Materiality of Prehistoric Visual Practices: The Relevance of Maros–Pangkep Cave Paintings and Pasemah Megalithic Sculptures to Craft Traditions - Salma Rahmadani (Institut Seni Indonesia Padangpanjang, 2026)
This study analyzes the materiality of the Maros–Pangkep cave paintings and Pasemah megalithic statues and explains their conceptual relevance to craft traditions. It employed a qualitative approach using a literature review method. Secondary data, consisting of journal articles and scholarly books on the two forms of prehistoric heritage and theories of materiality, were analyzed descriptively and interpretively through data reduction, coding, thematic categorization, and interpretation. The results demonstrate that the use of rock surfaces, mineral pigments, and stone as sculptural material reflects empirical knowledge of material properties and mastery of painting and carving techniques. Materials did not merely serve as passive media but also influenced the techniques, visual forms, and creative processes. The artifacts also embody symbolic functions associated with group identity, beliefs, social activities, and human relationships with the environment, although their meanings must be interpreted according to the context of each site. The relevance of these visual practices to craft traditions lies in their use of natural materials, manual skills, and direct engagement between makers and materials. This relevance is conceptual and does not constitute evidence of direct genealogical continuity between prehistoric visual practices and craft traditions.